Pedagogical Aspects Of Systematic Organization Of Human Capital Management In Higher Education - Zamira Aminjonovna Normatova (Euro Asian Journal Publishing, 2024)
In this article, the management of human capital in the higher education system is explained in its scientific-theoretical aspects, and the pedagogical factors of integrating human resources into the content of continuous education and implementing them in practice are analyzed.
Keywords: human capital; pedagogical factors; intelligence